2022
DOI: 10.1002/sd.2438
|View full text |Cite
|
Sign up to set email alerts
|

The AI ESG protocol: Evaluating and disclosing the environment, social, and governance implications of artificial intelligence capabilities, assets, and activities

Abstract: AI and data are key strategic resources and enablers of the digital transition. Artificial Intelligence (AI) and data are also intimately related to a company's environment, social, and governance (ESG) performance and the generation of sustainability related impacts. These impacts are increasingly scrutinized by markets and other stakeholders, as ESG performance impacts both valuation and risk assessments. It impacts an entity's potential to contribute to good, but it also relates to risks concerning, for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…Early research results have mostly focused on the relationship with enterprises from the three dimensions of environment, society, and corporate governance. Saetra found that corporate governance is not objectionable to enhancing enterprise value, although the relationship between environmental and social factors and enterprise value is unclear [25]. However, the finding that higher levels of environmental and social responsibility enhance enterprise value is most common.…”
Section: Research Reviewmentioning
confidence: 99%
“…Early research results have mostly focused on the relationship with enterprises from the three dimensions of environment, society, and corporate governance. Saetra found that corporate governance is not objectionable to enhancing enterprise value, although the relationship between environmental and social factors and enterprise value is unclear [25]. However, the finding that higher levels of environmental and social responsibility enhance enterprise value is most common.…”
Section: Research Reviewmentioning
confidence: 99%
“…These digital technologies play a crucial role in accurate ESG reporting, and ESG investment is associated with AI capabilities (Saxena et al, 2023). In addition, Sætra (2023) argues that the AI ESG protocol is a solution for ESG assessment and disclosure. D’Amato et al (2022) employed a machine learning approach to assess the effect of financial balance sheets on the ESG score.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…sustainability information), the limited scope of non-financial disclosures imposed by the accounting regulation as well as the lack of external attestation bodies aimed to verify the declarative information embedded in the non-financial report (Czaja-Cieszyńska et al, 2021). In addition, Saetra (2022) addressed the problems of variability in the sustainability-related data produced by the requirements to collect and report sustainability-related information, which differ between nations, regions, and sectors. Due to…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%